Determinação multirresíduo de agrotóxicos em tomate, beterraba e cenoura empregando QuEChERS modificado e UHPLC-MS/MS - Stringhini, Fabiane Marconato (2020)
Beet, carrot and tomato are foods with a high content of water, sugars and pigments, which are among the most cultivated and consumed vegetables worldwide and frequently contain pesticide residues. Therefore, a simple multiresidue method was developed and validated to determine 129 pesticides and metabolites in beet, carrot and tomato samples using a modified acetate QuEChERS without clean-up for sample preparation and determination by ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS). Different sorbents and sorbent combinations were tested for the clean-up step, in addition to gravimetric and solvent evaporation tests. However, aiming a faster and cheaper method, it was decided to eliminate the clean-up step. Dilution of the raw extract in different proportions of mobile phase was evaluated and a dilution of 10 times presented adequate results improving analysis performance while minimizing the matrix effect. Validation performed according to SANTE guideline presented satisfactory results. Practical method limit of quantification was 10 μg kg-¹ for most compounds. Recoveries between 70 and 120% with precision ≤20% were found for most compounds and spike levels evaluated. Matrix effect results for tomato were not significant for most compounds. Method proved to be simple, robust and effective to be applied in routine analysis. Method applicability was performed by analysis of samples commercialized in Brazil and positive results were found demonstrating the importance of the proposed method.